află necunoscutul: (y+5×5)-6×6=40÷2+3, (a+8×2+6×8)-8×9+8×8=6×10+2×4.
Răspunsuri la întrebare
Răspuns de
3
Răspuns:
Explicație pas cu pas:
( y + 5 x 5) - 6 x 6 = 40 : 2 + 3
( y + 25 ) - 36 =20 +3
( y + 25 ) - 36 =23
y+ 25 = 23+36
y + 25 =59
y =59- 25
y=34
( a + 8 x 2 +6 x 8) - 8 x 9+8 x 8=6 x 10 +2 x 4
( a+16 +48) - 8 x 9 + 8 x 8=6 x 10 + 2 x 4
(a + 16+ 48 ) -72 + 64 =60 + 8
( a + 16 + 48 ) - 72 + 64 = 68
( a + 16 + 48) -72=68 - 64
( a + 16 +48 ) - 72=4
( a + 16 + 48 ) =72 + 4
a + 16 +48 =76
a+ 16= 76-48
a+16= 28
a=28-16
a=12
Răspuns de
1
( y + 5 × 5 ) - 6 × 6 = 40 : 2 + 3
( y + 25 ) - 36 = 20 + 3
( y + 25 ) - 36 = 23
y + 25 = 23 + 36
y + 25 = 59
y = 59 - 25
y = 34
Verificare :
( 34 + 5 × 5 ) - 6 × 6 = 40 : 2 + 3
( 34 + 25 ) - 36 = 20 + 3
59 - 36 = 23
( a + 8 × 2 + 6 × 8 ) - 8 × 9 + 8 × 8 = 6 × 10 + 2 × 4
( a + 16 + 48 ) - 72 + 64 = 60 + 8
( a + 16 + 48 ) - 72 + 64 = 68
( a + 16 + 48 ) - 72 = 68 - 64
( a + 16 + 48 ) - 72 = 4
a + 16 + 48 = 4 + 72
a + 16 + 48 = 76
a + 16 = 76 - 48
a + 16 = 28
a = 28 - 16
a = 12
Verificare :
( 12 + 8 × 2 + 6 × 8 ) - 8 × 9 + 8 × 8 = 6 × 10 + 2 × 4
( 12 + 16 + 48 ) - 72 + 64 = 60 + 8
( 28 + 48 ) - 72 + 64 = 68
76 - 72 + 64 = 68
4 + 64 = 68
( y + 25 ) - 36 = 20 + 3
( y + 25 ) - 36 = 23
y + 25 = 23 + 36
y + 25 = 59
y = 59 - 25
y = 34
Verificare :
( 34 + 5 × 5 ) - 6 × 6 = 40 : 2 + 3
( 34 + 25 ) - 36 = 20 + 3
59 - 36 = 23
( a + 8 × 2 + 6 × 8 ) - 8 × 9 + 8 × 8 = 6 × 10 + 2 × 4
( a + 16 + 48 ) - 72 + 64 = 60 + 8
( a + 16 + 48 ) - 72 + 64 = 68
( a + 16 + 48 ) - 72 = 68 - 64
( a + 16 + 48 ) - 72 = 4
a + 16 + 48 = 4 + 72
a + 16 + 48 = 76
a + 16 = 76 - 48
a + 16 = 28
a = 28 - 16
a = 12
Verificare :
( 12 + 8 × 2 + 6 × 8 ) - 8 × 9 + 8 × 8 = 6 × 10 + 2 × 4
( 12 + 16 + 48 ) - 72 + 64 = 60 + 8
( 28 + 48 ) - 72 + 64 = 68
76 - 72 + 64 = 68
4 + 64 = 68
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Fizică,
8 ani în urmă
Matematică,
9 ani în urmă
Engleza,
9 ani în urmă
Matematică,
9 ani în urmă